2014
DOI: 10.1074/jbc.m113.536607
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin13 Expression Is Regulated by Mammalian Target of Rapamycin (mTOR) in Injured Neurons to Promote Axon Regeneration

Abstract: Background: Axon regeneration following nerve injury depends on activation of mTOR. Results: Nerve injury increases the expression of syntaxin13 in an mTOR-dependent manner. Conclusion: Injury-induced synthesis of syntaxin13 is important for axon regeneration. Significance: Learning which proteins are synthesized via mTOR in injured nerves is crucial to our understanding of regenerative mechanisms in peripheral neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 58 publications
1
19
1
Order By: Relevance
“…Newly synthesized proteins that contribute to the regeneration process include cytoskeletal proteins (42) and membrane-associated proteins (43,44). Here we reveal that local translation of filamin A contributes to control of the spatial activity of HDAC5 in injured axons.…”
Section: Discussionmentioning
confidence: 89%
“…Newly synthesized proteins that contribute to the regeneration process include cytoskeletal proteins (42) and membrane-associated proteins (43,44). Here we reveal that local translation of filamin A contributes to control of the spatial activity of HDAC5 in injured axons.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, their expression is also required for the biogenesis of PMEL-positive premature melanosomes. Previous studies in non-melanocytes have shown that STX13 is required for recycling of transferrin receptor and other cargo to cell surface ( Prekeris et al, 1998 ), homotypic endosome fusion ( McBride et al, 1999 ), phagophore maturation ( Lu et al, 2013 ) and axon regeneration during nerve injury ( Cho et al, 2014 ). By contrast, VAMP7 is involved in the fusion of late endosomes with lysosomes ( Chaineau et al, 2009 ), delivery of GLUT1 to plasma membrane along with retromer ( Hesketh et al, 2014 ), membrane repair ( Rao et al, 2004 ), neurite outgrowth ( Martinez-Arca et al, 2000 ) and fusion of autophagosomes with lysosomes ( Fader et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K-Akt regulates local protein synthesis in the axon through the mTOR pathway, where adult CNS neurons require mTOR signaling for axon regeneration (31, 87, 88). Quantitative mass spectrometry identified syntaxin13 as a protein locally synthesized by activated mTOR in the axon (89). Knockdown of syntaxin13 in culture prevented axon growth and regeneration.…”
Section: Importance Of Proteomics In Identifying Mechanismsmentioning
confidence: 99%